Personal Income Taxation in Poland - Małecka-Zieńska, Edyta (Ekonomika, 2008)
The Polish taxation system has been undergoing substantial changes in recent years, aimed at creating a more transparent system and conforming to the taxation standards of market economy countries. The two most important changes were introduction of the personal income tax (PIT) in 1992 and replacement of the turnover tax with the value added tax (VAT) in 1993. The uniform personal income tax covered all incomes generated by natural persons irrespective of where the sources of income are located. The reform provided also a more equitable distribution of the tax burden by introducing a progressive system with three nominal tax rates (in 1992-20%, 30%, 40%).A comparative study of the effective PIT rate for pensioners and other groups of PIT payers is the main goal of this paper. The study refers to our own research on data received from The information of Polish Ministry of Finance about accounting of PIT in several subsequent years. Statistics cover a period from 1993 to 2003. However, numbers of taxpayers refer also to year 1992 when the PIT has been established and a period from 2004 to 2006.Concluding the situation in Poland, taxpayers with the highest income make exhaustive use of tax reductions. There are occurring situations when well-off people benefit more than people with relatively minor income (e. g. pensioners). It happens even if most of deductions were aimed generally at all taxpayers. Such a situation reduces the impression of the system fairness. Because tax deductions reduce budgetary revenues, the foregone revenues have to be compensated by other taxes or / and higher rates. Therefore, the system of deductions and relief, on the one hand, supports the special gains (e. g. house building), however, on the other it generates costs. It is possible that the reduction of tax rate for the I tax bracket and removal of some tax exemptions and deductions would make the Polish personal income tax more transparent, equal and simple.